Natural and anthropogenic disasters vulnerability, preparedness, and mitigation - Jha, Madan Kumar (The Netherlands Springer, 2010)
Contributed articles.
Includes bibliographical references and index.
Keywords: Disasters; Disaster relief; Emergency management; Natural disasters